2007
DOI: 10.1044/1058-0360(2007/040)
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Language Profiles of School-Age Children With Autism Spectrum Disorders and Williams Syndrome

Abstract: The CCC-2 appears to provide an effective means to identify and characterize pragmatic language difficulties using a standardized approach in children with ASD and WS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 47 publications
(84 reference statements)
6
79
0
10
Order By: Relevance
“…Pragmatic language skills may play a similar role, but very few studies have examined pragmatic profiles. Recent work (Philofsky et al 2007) used the Children's Communication Checklist-Version 2 (CCC-2; Bishop 2003), a parent report checklist designed to evaluate communicative competence, to compare detailed pragmatic profiles of children with ASD and children with Williams' Syndrome. They found that there were both similarities and differences in pragmatic profile between the groups, but they did not relate these findings to measured differences in other language domains, or to differences in adaptive functioning.…”
mentioning
confidence: 99%
“…Pragmatic language skills may play a similar role, but very few studies have examined pragmatic profiles. Recent work (Philofsky et al 2007) used the Children's Communication Checklist-Version 2 (CCC-2; Bishop 2003), a parent report checklist designed to evaluate communicative competence, to compare detailed pragmatic profiles of children with ASD and children with Williams' Syndrome. They found that there were both similarities and differences in pragmatic profile between the groups, but they did not relate these findings to measured differences in other language domains, or to differences in adaptive functioning.…”
mentioning
confidence: 99%
“…Whilst not diagnostic, it can be used in screening for a potential communication conditions (e.g., ASC and specific language impairment-SLI). For the purposes of this study two CCC-2 indices were (see Philofsky, Fidler, & Hepburn, 2007). Firstly, to assess the use of language for social purpose, pragmatic language composite -CCC-2 PRAG -based on the sum of 4 CCC-2 scales assessing Context, Stereotyped Language, Non-Verbal Communication and Appropriate Initiation was derived.…”
Section: Measures Of Verbal Ability and Socio-communicative Competencementioning
confidence: 99%
“…Informal tests that depend on parents' reports and observations regarding their children seem to be more effective in measuring pragmatic ability. Philofsky, Fidler, & Hepburn (2007) have used the second version of the Children's Communication Checklist (CCC-2) to simultaneously measure and compare PLIs in children with two types of syndromes: autism spectrum disorder ASD and William's syndrome WS. The CCC-2 was found to be an effective tool for identifying, measuring and comparing groups of children with PLIs.…”
Section: International Journal Of Linguisticsmentioning
confidence: 99%